Effects of Bisphenol A on Foxl2 gene expression and DNA damage in adult viviparous fish Goodeaatripinnis. Issue 3 (1st February 2020) - Cervantes-Camacho, Isabel; Guerrero-Estévez, Sandra M.; López, María Fernanda; Alarcón-Hernández, Ernesto; López-López, Eugenia
ABSTRACT: Bisphenol A (BPA) is an emerging pollutant of global concern. Viviparous fish Goodea atripinnis is endemic to the Central Mexican Plateau where BPA was detected; however, few studies examined the influence of this chemical on native viviparous fish. The effects of BPA (sublethal dose) were determined on DNA integrity and Foxl2 expression in G. atripinnis gonads, and interactions of BPA with FOXL2 protein. Genotoxicity analysis revealed that % comets, at 14 and 28 days and comet tail length (at 14 days) were significantly higher in exposed compared to controls. In general, the % DNA tail was not markedly higher in BPA-treated fish; however, tail moment related to tail length exhibited significant increases in DNA damage. RT-qPCR assays showed Foxl2 overexpression after 14 and 28 days of exposure in females; while in males, Foxl2 was overexpressed after 28 days. In silico analysis demonstrated that BPA interacted with seven residues located in FOXL2 homeodomain. In summary, sublethal BPA doses induced DNA damage and changes in Foxl2 expression in gonadal cells of G. atripinnis, which may adversely affect reproduction in BPA-exposed wild populations. Foxl2 overexpression and BPA-FOXL2 interaction suggested alterations in processes involving Foxl2 . Viviparous fish may thus serve as potential non-conventional models for assessing pollutants effects.